An integrated in vitro approach on the enzymatic and antioxidant mechanisms of four commercially available essential oils (Copaifera officinalis, Gaultheria fragrantissima, Helichrysum italicum, and Syzygium aromaticum) traditionally used topically for their anti-inflammatory effects - Cebollada, Pilar; Gomes, Nelson G. M.; Andrade, Paula B.; López, Víctor (Frontiers in Pharmacology, 2024)
Despite the increasing number of essential oils being reported on their potential therapeutic effects, some remain relatively unknown on their biological properties. That is the case of the essential oils obtained from copaiba (Copaifera officinalis L.), wintergreen (Gaultheria fragrantissima Wall.), everlasting (Helichrysum italicum (Roth) G.Don) and clove (Syzygium aromaticum (L.) Merr. & L.M.Perry), commonly labelled as being useful on the amelioration of conditions with an inflammatory background. To further broaden the current knowledge on the four essentials, commercially available samples were approached on their effects upon a series of mediators that are involved on the inflammatory and oxidative response, both through in vitro cell-free and cell-based assays (5lipoxygenase activity, lipid peroxidation, free radical and nitric oxide radical scavenging properties or tyrosinase inhibition). The four oils proved to be active at some of the concentrations tested in most of the performed assays. Significant differences were found between the essential oils as Syzygium aromaticum proved to be the most active essential oil, followed by Gaultheria fragrantissima against 5-LOX and linoleic acid peroxidation, proving their potential use as antioxidants and antiinflammatory agents. In fact, the IC50 of Syzygium aromaticum in the LOX assay was 62.30 µg mL -1 . Besides Syzygium aromaticum efficiently scavenged superoxide radicals generated by xanthinexanthine oxidase, displaying an IC50 135.26 µg mL -1 . Helichrysum italicum exhibited a significant decrease in the nitric oxide levels on BV-2 cells, showing its potential as a cytoprotective agent against toxic damage. Copaiba oil was the best sample acting as tyrosinase inhibitor, exhibiting an IC50 98.22 µg mL -1 . More studies are needed to describe the essential oils properties, but these results confirm the potential of essential oils as anti-inflammatory and antioxidant agents.